PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DANA BAGI HASIL TERHADAP BELANJA MODAL - Febriana Kiranti, 14.05.52.0008; Maryono, Maryono (Students' Journal of Accounting and Banking, 2018)
This study examines the impact of Local Personal Income, General Allocation Funds, Special Allocation Funds, and Profit Sharing Funds on Capital Expenditures. The population in this study is the district or city government in Central Java. The population in this study is the district or municipal government in Central Java region as many as 35 districts or cities. Data using secondary data that has been taken from budget realization report in central java 2014-2016. This research is a population with data collection method is done by documentary method. Keywords : Local Own Revenue, General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, and Capital Expenditures